(untitled) (Research, Society and Development, 2021)
This paper aimed to reflect on the practices adopted by a speech therapist in the care of two children with learning difficulties. For that, the conceptions of language and subject were taken critically from the interactionist theorization, in order to establish a contrast between Traditional Speech Therapy and the Language Clinic. The speech therapy sessions were filmed, transcribed and analyzed according to the premises of the Language Clinic, therefore adopting a qualitative and descriptive methodology. The data selected for investigation referred to the moments when the therapist corrected errors in the children’s speech, reading and writing. During the speech therapy sessions, the pedagogical position of the therapist stood out, so that the child was placed in the position of learner and the speech therapist in the position of who teaches and corrects, showing practices related to Traditional Speech Therapy. After listening to the transcriptions, the therapist could distance herself from the clinical scene, reinterpret the linguistic manifestations of children (not only as errors or hits) and, therefore, critically review her practice. Listening to the transcription of the sessions promoted a change in the therapist’s position in relation to her own speech and that of the children. The option for the methodology proposed by the Language Clinic allowed us to conclude that the pedagogical position is not a necessary position for speech therapy practice.